2021
DOI: 10.3390/microorganisms9122575
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Decontamination of a Specialist Transport System for Patients with High Consequence Infectious Diseases

Abstract: When transferring highly infective patients to specialist hospitals, safe systems of work minimise the risk to healthcare staff. The EpiShuttle is a patient transport system that was developed to fit into an air ambulance. A validated decontamination procedure is required before the system can be adopted in the UK. Hydrogen peroxide (H2O2) vapour fumigation may offer better penetration of the inaccessible parts than the liquid disinfectant wiping that is currently suggested. To validate this, an EpiShuttle was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…These studies have demonstrated both antimicrobial efficacy and repeatability, which provides confidence in the use of HPV for decontamination. Furthermore, commercially available automated HPV disinfection systems can deliver concentrations of the fumigant required to achieve the criteria stated in the EN17272 standard [ 64 ]. The EN17272 is a European standard for determining the disinfectant activity of airborne room disinfection by automated processes and covers vegetative bacteria, mycobacteria, bacterial spores, yeasts, fungal spores, viruses and bacteriophages [ 65 ].…”
Section: Application Of Hydrogen Peroxide Vapour Against Clinically R...mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have demonstrated both antimicrobial efficacy and repeatability, which provides confidence in the use of HPV for decontamination. Furthermore, commercially available automated HPV disinfection systems can deliver concentrations of the fumigant required to achieve the criteria stated in the EN17272 standard [ 64 ]. The EN17272 is a European standard for determining the disinfectant activity of airborne room disinfection by automated processes and covers vegetative bacteria, mycobacteria, bacterial spores, yeasts, fungal spores, viruses and bacteriophages [ 65 ].…”
Section: Application Of Hydrogen Peroxide Vapour Against Clinically R...mentioning
confidence: 99%
“…In addition, it must be noted that the entire processing workflow from collection to post-processing, as demonstrated by Grossman et al [ 111 ], which allowed healthcare workers to keep their own N95 respirators in a large academic metropolitan healthcare system, was accomplished in less than 24 h. Bailey et al [ 64 ] validated the decontamination of a specialist transport system for patients with high-consequence infectious diseases, “EpiShuttle” (a patient transport system designed to fit into air ambulance), using HPV fumigation. The authors [ 64 ], upon decontamination with HPV, achieved a complete kill of all pathogens with the use of a commercially available Bioquell HPV system, achieving a 6 log 10 reduction in Geobacillus stearothermophilus ATCC 12980 endospores, alongside organic liquid suspensions and dried surface samples of MS2 bacteriophage. However, it is important to note that HPV fumigation can be less efficient if larger amounts of biological fluids are present on the surface due to its limited penetration.…”
Section: Hydrogen Peroxide Vapour As a Biocide For Reuse Of N95/ffp2 ...mentioning
confidence: 99%
See 1 more Smart Citation